Inbred mouse strains differentially susceptible to Leishmania donovani infection differ in their immune cell metabolism. (December 2018) - Bodhale, Neelam Prakash; Pal, Subhashis; Kumar, Sunil; Chattopadhyay, Debprasad; Saha, Bhaskar; Chattopadhyay, Naibedya; Bhattacharyya, Maitree
Highlights: 129/Sv mice are resistant but BALB/c mice are susceptible to Leishmania donovani . IL-10 spleen is less in L. donovani -infected 129/Sv, but high in BALB/c, mice. Glycolytic enzymes expression correlate with resistance to L. donovani infection. Abstract: Leishmania donovani is a protozoan parasite that infects mammalian macrophages, wherein the parasite resides and replicates as amastigotes, inflicting the potentially fatal disease visceral leishmaniasis. The disease is characterized by severe immunosuppression and hypocholesterolemia implying metabolic changes in L. donovani infection; whether such metabolic changes are also linked to susceptibility to the infection is not known. Herein, four inbred mouse strains were first characterized for their resistance or susceptibility profile to L. donovani infection. It was observed that these four mouse strains were differentially susceptible to L. donovani infection. Splenic expression of four key cytokines– IL-10, IL-12, IFN-γ and IL-4- revealed that the differential susceptibility of these four mouse strains to L. donovani was partially associated with these cytokines. The association was further correlated with the expression of different enzymes of the glycolytic pathway in the spleen of these L. donovani -infected mice. Thus, the observations reported here suggest an association between host metabolism, cytokine secretion profile and L. donovani susceptibility. As the chemotherapeutic choices are extremely limited and a vaccine for human use is yet to be discovered for the neglected tropical disease that is prevalent in 88 countries affecting 320 million people, this metabolic study is a significant research area that has potentials to develop a new target for anti-leishmanial chemotherapy.